Validated Impacts of N6-Methyladenosine Methylated mRNAs on Apoptosis and Angiogenesis in Myocardial Infarction Based on MeRIP-Seq Analysis - Zhang, Yingjie; Hua, Wenjie; Dang, Yini; Cheng, Yihui; Wang, Jiayue; Zhang, Xiu; Teng, Meiling; Wang, Shenrui; Zhang, Min; Kong, Zihao; Lu, Xiao; Zheng, Yu (Frontiers in Molecular Biosciences, 2022)
Objectives: N6-methyladenosine (m6A) is hypothesized to play a role in the regulation of pathogenesis of myocardial infarction (MI). This study was designed to compare m6A-tagged transcript profiles to identify mRNA-specific changes on pathophysiological variations after MI. Methods: N6-methyladenosine methylated RNA immunoprecipitation sequencing (MeRIP-seq) and RNA sequencing (RNA-seq) were interacted to select m6A-modified mRNAs with samples collected from sham operated and MI rat models. m6A methylation regulated mRNAs were interacted with apoptosis/angiogenesis related genes in GeneCards. Afterwards, MeRIP-quantitative real-time PCR (MeRIP-qRT-PCR) was performed to measure m6A methylation level of hub mRNAs. m6A methylation variation was tested under different oxygen concentration or hypoxic duration in H9c2 cells and HUVECs. In addition, Western blot and qRT-PCR were employed to detect expression of hub mRNAs and relevant protein level. Flow cytometry and Tunel assay were conducted to assess apoptotic level. CCK-8, EdU, and tube formation assay were performed to measure cell proliferation and tube formation ability. Results: Upregulation of Mettl3 was firstly observed in vivo and in vitro, followed by upregulation of m6A methylation level. A total of 567 significantly changed m6A methylation peaks were identified, including 276 upregulated and 291 downregulated peaks. A total of 576 mRNAs were upregulated and 78 were downregulated. According to combined analysis of MeRIP-seq and RNA-seq, we identified 26 significantly hypermethylated and downregulated mRNAs. Based on qRT-PCR and interactive analysis, Hadh, Kcnn1, and Tet1 were preliminarily identified as hub mRNAs associated with apoptosis/angiogenesis. MeRIP-qRT-PCR assay confirmed the results from MeRIP-seq. With the inhibition of Mettl3 in H9c2 cells and HUVECs, downregulated m6A methylation level of total RNA and upregulated expression of hub mRNAs were observed. Increased m6A level was verified in the gradient context in terms of prolonged hypoxic duration and decreased oxygen concentration. Under simulated hypoxia, roles of Kcnn1 and Tet1 in angiogenesis and Hadh, Tet1, and Kcnn1 in apoptosis were further confirmed with our validation experiments. Conclusion: Roles of m6A-modified mRNA transcripts in the context of MI were preliminarily verified. In the context of m6A methylation, three hub mRNAs were validated to impact the process of apoptosis/angiogenesis. Our study provided theoretical basis and innovative targets for treatment of MI and paved the way for future investigations aiming at exploring upstream epigenetic mechanisms of pathogenesis after MI.